FROM DIFFUSE CONSTITUTIONAL REVIEW TO INJUNCTION MANDATE: MECHANISMS FOR THE REALIZATION OF THE RIGHT TO CAREER PROGRESSION WITHIN THE SCOPE OF MUNICIPAL PUBLIC SERVICE - Brito, Maria Victoria Souza Gonçalves; de Souza Junior , Mario Cleone; Delfim, Priscila Martins (Seven Editora, 2025)
This article examines the non-compliance by the municipal administration of Juazeiro/BA with the provisions of Law No. 2,606/2016, which establishes the Career, Positions and Remuneration Plan (PCCR) for employees of the Department of Education and Sports, especially regarding the percentages of horizontal progression (2.5%) and vertical/promotion (5%). Based on a lawsuit filed by Mailde Bonfim dos Santos Almeida and the counter-arguments to the appeal filed by the Municipality, the study demonstrates that such omission constitutes material unconstitutionality due to the absence of effective regulation, subject to ordinary judicial review and, ultimately, via Writ of Mandamus (art. 5, LXXI, CF/88). Through bibliographic review and documentary research within the scope of the STF (Supreme Federal Court), STJ (Superior Court of Justice), and TJ/BA (Court of Justice of Bahia), the performance of the Bahian Judiciary in recognizing administrative omission and ruling in favor of similar claims, imposing salary revisions and impacting ancillary benefits, is highlighted. The results reinforce the need for judicial intervention to fill normative gaps, guaranteeing the irreducibility of salaries and administrative efficiency. DOI: https://doi.org/10.56238/sevened2025.040-005